Pengembangan Kurikulum Sosiologi Agama sebagai Model dalam Pelaksanaan Merdeka Belajar bagi Mahasiswa Institut Agama Kristen Negeri Tarutung - Sudirman Lase; Elvri Teresia Simbolon; Jupalman Welly Simbolon; Harisan Boni Firmando; Roida Lumbantobing; Ade Putera Arif Panjaitan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The rapid development of the times no longer allows the world of education to be comfortable with the applicable curriculum. Responding to this challenge, the Ministry of Education and Culture launched the Independent Learning Campus policy. The Sociology of Religion Study Program at IAKN Tarutung chose one of the eight Merdeka Learning programs, namely internships. The chosen internship is an internship with a structured form, with the hope that students can actualize their knowledge at the internship location. This study aims to determine the implementation of the sociology of religion curriculum development as a model for the implementation of independent learning internships at IAKN Tarutung. This study uses a qualitative method with a descriptive approach. The methods of observation, interviews, document studies and focus group discussions were used to collect data. The results showed that the Independent Learning internship was going well, as evidenced by the learning outcomes of the apprenticeship courses and the soft skills of students in four villages in the Toba Caldera geosite area which is the location of the internship, where the majority of students received satisfactory grades from course lecturers and field supervisors. from partners. This study also evaluates the results of the internship implementation using a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) so that the implementation of internship activities will increase in the future.